2011
DOI: 10.1177/1090198111418108
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Parallel Process Model

Abstract: This article examines constructs, propositions, and assumptions of the extended parallel process model (EPPM). Review of the EPPM literature reveals that its theoretical concepts are thoroughly developed, but the theory lacks consistency in operational definitions of some of its constructs. Out of the 12 propositions of the EPPM, a few have not been tested explicitly and not a single one received unequivocal empirical support. This article proposes alternative operationalization for some of the constructs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(205 citation statements)
references
References 101 publications
(227 reference statements)
8
193
1
3
Order By: Relevance
“…When appraised as threatening, fear appeals result in higher test anxiety, a higher performance-avoidance goal (to avoid performing worse than one's classmates), lower intrinsic motivation, and lower grades on tests and examinations (Putwain & Best, 2011, 2012Putwain & Roberts, 2009;Putwain & Remedios, 2014b;Putwain & Symes, 2011a,2011bSprinkle, Hunt, Simonds, & Comadena, 2006). These findings are broadly consistent with those from adjacent areas of the educational psychology literature.…”
Section: Fear Appeals In the Classroomsupporting
confidence: 80%
See 3 more Smart Citations
“…When appraised as threatening, fear appeals result in higher test anxiety, a higher performance-avoidance goal (to avoid performing worse than one's classmates), lower intrinsic motivation, and lower grades on tests and examinations (Putwain & Best, 2011, 2012Putwain & Roberts, 2009;Putwain & Remedios, 2014b;Putwain & Symes, 2011a,2011bSprinkle, Hunt, Simonds, & Comadena, 2006). These findings are broadly consistent with those from adjacent areas of the educational psychology literature.…”
Section: Fear Appeals In the Classroomsupporting
confidence: 80%
“…The nascent literature examining the outcomes of fear appeals, used prior to high-stakes examinations, has shown that when fear appeals are appraised as threatening they result in a higher performance-approach goal, higher test anxiety, lower intrinsic motivation, and lower examination and test grades (Putwain & Best, 2011, 2012Putwain & Symes, 2011b;Sprinkle et al, 2006). The results of this study extend this body of work to show how attainment value and academic self-efficacy are also influenced by how fear appeals are appraised.…”
Section: The Outcome Of Fear Appeals Appraisalsupporting
confidence: 72%
See 2 more Smart Citations
“…A recent meta-analysis by Popova (2012), however, found a lack of consistency in the operationalisation of some of its main constructs; for example, fear has been operationalised as self-reported 'fright' or 'anxiety' and also through physiological changes. Questions have also been raised about whether susceptibility and severity (and response efficacy and self-efficacy) have an additive or multiplicative relationship (Popova, 2012). A broader limitation, however, lies in its focus on only fear-based persuasion (Maloney, Lapinski, & Witte, 2011;Popova, 2012).…”
Section: Critiques Of the Theoretical Underpinnings Of The Satmdtmentioning
confidence: 99%